Manajemen Kurikulum Program Speed Ta’lim di Madrasash Tsanawiyah Zainul Hasan Genggong: - Yuliana, Sri; Izzah, Ismatul; Hayati, Nur (Jurnal Administrasi Pendidikan Islam, 2024)
A special program for students with exceptional intelligence and talents is implemented to provide education services tailored to students' needs, as well as to create innovation and motivation. This research aims to analyze curriculum management practices in the speed ta'lim program at MTs Zainul Hasan Genggong. A qualitative approach is used in this research through data collection via interviews, observations, and document analysis. The results show that curriculum management at MTs Zainul Hasan Genggong is supported by systematic and planned management of various aspects, including planning, implementation, evaluation, and adjustment. The semester credit-based curriculum provides flexibility in planning learning programs, allowing adjustments to students' needs and curriculum developments periodically. Based on observation results, this research has been conducted in accordance with several predetermined requirements and conditions. The program implementation has met established standards, demonstrating suitability in providing education services oriented towards the needs of students with exceptional intelligence and talents. This study is expected to provide valuable insights for the development of similar programs in other educational institutions, as well as significant contributions to improving the quality of education for talented students.